2019
DOI: 10.1007/s10706-018-00791-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Passively Loaded Pile Groups

Abstract: Piled foundations could be affected negatively as a result of passive loadings caused by nearby soil movement-induced activities, and failure of piles could happen in some sever cases. This paper deals with the numerical analysis of passively loaded pile groups and piled raft in sand. The complexity involved in such problems due to pile-soil, pile-pile, pile-cap, soil-cap, and moving soil-stable soil interaction needs a powerful tool to make three dimensional analysis possible. In the current study, PLAXIS 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The bending moment that occurs at each depth is dependent on the pile condition [29]. In the case of a fixed long pile head, the bending moment converges to zero at the tip of the pile and changes in direction at the top and bottom of the pile [20]. Therefore, in our tests, the strain gauges of the pile were attached as shown in Figure 3 to determine the magnitudes of the bending moment and the location of bending moment at which the direction of the moment changed.…”
Section: Types and Locations Of Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bending moment that occurs at each depth is dependent on the pile condition [29]. In the case of a fixed long pile head, the bending moment converges to zero at the tip of the pile and changes in direction at the top and bottom of the pile [20]. Therefore, in our tests, the strain gauges of the pile were attached as shown in Figure 3 to determine the magnitudes of the bending moment and the location of bending moment at which the direction of the moment changed.…”
Section: Types and Locations Of Sensorsmentioning
confidence: 99%
“…Hokmadadi et al (2014) assessed the validity of the numerical analysis approach by comparing the results obtained from model shaking table testing and numerical analysis [19]. Ihsan and Tahsin (2019) compared the results of experimental and numerical analysis of piles subjected to passive loading and revealed that the numerical results overestimated deflection but produced reasonably consistent bending moments [20]. Although more accurate p-y curves based on studies of soil-structure interaction (SSI) under dynamic load conditions have been proposed, such studies have assumed that the superstructure is an SDOF structure [4,10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the lateral response of the pile adjacent to surcharge loading, such as laboratory tests (Al-abboodi et al, 2020;Toma Sabbagh et al, 2020), finite element method (Xu and Poulos, 2001;Karim, 2013;Al-abboodi and Sabbagh, 2019), and theoretical approach (Springman, 1989;Zhang et al, 2020a;Bellezza, 2020;Zhang et al, 2020b). The laboratory tests, numerical method, and theoretical analysis (Chen and Poulos, 1997;Ellis and Springman, 2001;Abo-Youssef et al, 2021;Ramalakshmi, 2021) proved that the effect of movement soil would lead to large deformation or even failure of the pile.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2020b) proposed a load transfer model for analyzing the pile-soil interaction and provided a semi-analytical solution. Al-abboodi and Sabbagh (2019) used Plaxis3D to investigate the group piles under soil movement in sand layers and identified a discrepancy between the predicted and test results. However, the study did not properly consider the relative lateral displacement between pile and soil and the density variation of sand.…”
Section: Introductionmentioning
confidence: 99%